Thermos Ability in Maintaining Crystalloid Liquid Temperature (Ringerâ€™s Lactate and Normal Saline 0,9%): an Alternative in Maintaining Resuscitation Fluid Temperature - Ninda Saputri; Abdurrahman Wahid; Tina Handayani Nasution; Gia Eka Negara (Journal of Nursing Science Update (JNSU), 2021)
Haemorrhagic shock should be treated with fluid therapy at 390Â°C to avoid hypothermia. Storage of infusion fluid in a rice thermos is one method to maintain the temperature of the infusion fluid. This study aimed to determine the effect of using a thermos to maintain a temperature of 390C crystalloid liquid (ringer lactate and normal saline 0,9%) at a room temperature of 250C. This research method uses experimental quantitative (pre-experimental) with a one-shot case study design. Six bottles of Ringer's lactate and six bottles of normal saline 0,9% were warmed to 390C, then stored in a rice thermos at 250C and the temperature changes were measured for 6 hours. A digital thermometer was used to take measurements. The Mann-Whitney test was used to analyze the data. The results show that the temperature of Ringer's lactate fluid was reduced by an average of 4,60C, and normal saline was reduced by an average of 4,30C. There was a significant difference in temperature changes in the ringer's lactate fluid and normal saline 0,9% (p=0,000;Î±=0,05). The results of the study were that the rice thermos was able to maintain the temperature of ringer's lactate fluid at 390C for 96 minutes and normal saline 0,9% for 78 minutes, while to prevent hypothermia (360C) ringer's lactate fluid for 4 hours 59 minutes and normal saline 0,9 % for 4 hours 55 minutes.